2019
DOI: 10.1590/2179-8087.037518
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Behavior and Pollen Viability of Spondias mombin L.: Native Fruit Species of the Amazon

Abstract: Spondias mombin L. is a fruit species native to the Amazon with great marketing potential. The aim of this study was to examine the meiotic behavior and pollen viability of S. mombin. Flower buds at various developmental stages were collected for analyses of pollen viability, in vitro germination, and meiotic behavior. S. mombin is diploid with 2n = 2x = 30 chromosomes. Meiosis showed to be regular, with only 13.3% of cells with abnormal division. A high meiotic index was found: 96.5%. Pollen viability did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…S. mombin (2n = 2x = 30) reproduces by cross-pollination performed mainly by bees, and it also presents vegetative propagation. Furthermore, it presents protandrous dichogamy and a high value of the pollen/ovule ratio (Ramos 2009;Zortéa et al 2019). The species is classi ed as andromonoecious (Ramos 2009), having staminate and hermaphrodite owers arranged in in orescences of the terminal pyramidal panicles type (Coradin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mombin (2n = 2x = 30) reproduces by cross-pollination performed mainly by bees, and it also presents vegetative propagation. Furthermore, it presents protandrous dichogamy and a high value of the pollen/ovule ratio (Ramos 2009;Zortéa et al 2019). The species is classi ed as andromonoecious (Ramos 2009), having staminate and hermaphrodite owers arranged in in orescences of the terminal pyramidal panicles type (Coradin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(2009) with four yellow mombin populations from Pernambuco assessed with nine isoenzyme loci, the values for genetic diversity ranged from 0.530 to 0.574. Using SSR markers,Zortéa et al (2019) found values ranging from 0.199 to 0.486, with a mean of He = 0.335, for populations in Mato Grosso, Midwest region. A study with three populations from the north of the State of Mato Grosso based on 14 ISSR primers identi ed genetic diversity values ranging from 0.20 to 0.24(Silva et al 2017b).…”
mentioning
confidence: 99%